Analysis of the Implementation of Accrual-Based Government Accounting Standards in the Financial Statements of Medan City Government - Putri Kemala Lubis; Khairani Matondang; Donita Nababan Nababan; Nursandi Sihombing; Reginta Barus (Outline Journal of Economic Studies, 2026)
Purpose: This study aims to analyze the application of accrual-based Government Accounting Standards (GAS) in the financial statements of the Medan City Government. The implementation of accrual-based SAP is the government's effort to improve the quality of transparent and accountable financial reports in accordance with applicable regulations. Methods: The method used in this study is qualitative, using a literature review approach and secondary data obtained from previous research and official data from the Central Statistics Agency (BPS). Results: Accrual-based Government Accounting Standards (GAS) is an accounting system that recognizes revenue, expenses, assets, liabilities, and equity in comprehensive financial reporting, thereby providing a more accurate picture of the financial condition. The results of the study indicate that the implementation of accrual-based SAP in regional government financial reports has generally been successful and in accordance with applicable standards. This is demonstrated by increasingly structured regional financial management and improvements in the transparency and accountability of financial reports. Data on Medan City's regional revenue realization in 2020 also indicates that the regional government has managed its finances quite well to support the implementation of government activities. Conclusions: Thus, the implementation of accrual-based SAP has an important role in improving the quality of local government financial reports and supporting the creation of good governance.